'Those tablets, they are finding an empty stomach': a qualitative investigation of HIV risk among sexual and gender minority migrants in Cape Town, South Africa. Issue 4 (19th May 2022) - Alessi, Edward J.; Kahn, Sarilee; Giwa, Sulaimon; Cheung, Shannon
ABSTRACT : Objectives: HIV prevalence among sexual and gender minority (SGM) individuals in South Africa is among the highest in the world; however, SGM migrants, an especially vulnerable subgroup of both the SGM and migrant populations, have frequently been overlooked in the country's robust public health response. This qualitative study, guided by syndemics theory, explored the processes by which SGM migrants in South Africa are exposed to HIV risk and those that may reduce this risk. Design: We conducted 6 focus groups with a total of 30 SGM migrants living in Cape Town. Participants were men who have sex with men, women who have sex with women, and transgender women. Transcripts were analyzed using grounded theory. Results: Participants identified a number of interrelated factors (insecure immigration status, financial and housing instability, food insecurity, stigma and discrimination, and lack of social support) contributing to HIV risk. While some took PrEP or HIV medication, adherence could be affected by structural and psychosocial barriers. Conclusion: Interventions that respond to the syndemic impacts on HIV outcomes are needed to reduce disease burden among SGM migrants in South Africa.